How do you evaluate # e^( ( 13 pi)/4 i) - e^( ( 7 pi)/6 i)# using trigonometric functions?

Answer 1

# \qquad \qquad \qquad e^{ {13\pi}/4 i } - e^{ {7\pi}/6 i } \ = \ - 1/2 ( [ sqrt{2} + \sqrt{3} ] - [ \sqrt{2} + 1 ] i ). #

# "Recall the definition of the complex exponential:" #
# \qquad \qquad \qquad \qquad \qquad \qquad \qquad e^{ i \theta } \ = \ cos(\theta) + i sin(\theta). #
# "Using this with the given expression, we have:" #
# \qquad \qquad \qquad e^{ {13\pi}/4 i } - e^{ {7\pi}/6 i } \ = #
# [ cos( {13\pi}/4 ) + sin( {13\pi}/4 ) i ] - [ cos( {7\pi}/6 ) + sin( {7\pi}/6 ) i ] \ =#
# [ cos( {13\pi}/4 ) + cos( {7\pi}/6 ) ] - [ sin( {13\pi}/4 )+ sin( {7\pi}/6 ) ] i. #
# :. \qquad \ \ e^{ {13\pi}/4 i } - e^{ {7\pi}/6 i } \ = #
# [ cos( {13\pi}/4 ) + cos( {7\pi}/6 ) ] - [ sin( {13\pi}/4 )+ sin( {7\pi}/6 ) ] i. \quad \ (1) #
# "Now we must calculate the trig values in the above:" #
# \qquad \ cos( {13\pi}/4 ), \qquad sin( {13\pi}/4 ); \qquad cos( {7\pi}/6 ), qquad sin( {7\pi}/6 ). \qquad \ (2) #
# "For the first two trig values we note:" #
# cos( {13\pi}/4 ) \ = \ cos( 13/4 \pi ) \ = \ cos( [3 1/4] \pi ) #
# \qquad \qquad \qquad \qquad \qquad = \ cos( [ 2 + 1 1/4] \pi ) \ = \ cos( 2 \pi + [1 1/4] \pi ) #
# \qquad \qquad \qquad \qquad \qquad = \ cos( [ 1 1/4] \pi ) \ = \ cos( \pi + 1/4 \pi ) #
# \qquad \qquad \qquad \qquad \qquad = \ - cos( 1/4 \pi ), \qquad \qquad "as" \quad \pi + 1/4 \pi \ \in \ "Quadrant III" #
# \qquad \qquad \qquad \qquad \qquad = \ - cos( 45^@ ) #
# \qquad \qquad = \ - \sqrt{2} / 2, \qquad \quad "remembering the 45-45-90 right triangle." #
# "Similarly, proceeding with" \quad sin( {13\pi}/4 ), "we summarize:" #
# sin( {13\pi}/4 ) \ = \ sin( \pi + 1/4 \pi ) #
# \qquad \qquad \qquad \qquad \qquad = \ - sin( 1/4 \pi ), \qquad \qquad "as" \quad \pi + 1/4 \pi \ \in \ "Quadrant III" #
# \qquad \qquad \qquad \qquad \qquad = \ - sin( 45^@ ) #
# \qquad \qquad = \ - \sqrt{2} / 2, \qquad \quad "remembering the 45-45-90 right triangle." #
# "So we have:" #
# \qquad \qquad \quad cos( {13\pi}/4 ) \ = \ - \sqrt{2} / 2, \qquad \qquad sin( {13\pi}/4 ) \ = \ - \sqrt{2} / 2. \quad (3) #
# "Now, for the last two trig values in line (2) we note:" #
# cos( {7\pi}/6 ) \ = \ cos( 7/6 \pi ) \ = \ cos( [1 1/6] \pi ) #
# \qquad \qquad \qquad \qquad \qquad = \ cos( [ 1 + 1/6 ] \pi ) \ = \ cos( \pi + 1/6 \pi ) #
# \qquad \qquad \qquad \qquad \qquad = \ - cos( 1/6 \pi ), \qquad \qquad "as" \quad \pi + 1/6 \pi \ \in \ "Quadrant III" #
# \qquad \qquad \qquad \qquad \qquad = \ - cos( 30^@ ) #
# \qquad \qquad = \ - \sqrt{3} / 2, \qquad \quad "remembering the 30-60-90 right triangle." #
# "Similarly, proceeding with" \quad sin( 1/6 \pi ), "we summarize:" #
# sin( 7/6 \pi ) \ = \ sin( \pi + 1/6 \pi ) #
# \qquad \qquad \qquad \qquad \qquad = \ - sin( 1/6 \pi ), \qquad \qquad "as" \quad \pi + 1/6 \pi \ \in \ "Quadrant III" #
# \qquad \qquad \qquad \qquad \qquad = \ - sin( 30^@ ) #
# \qquad \qquad = \ - 1 / 2, \qquad \quad \ \ \ "remembering the 30-60-90 right triangle." #
# "So we have:" #
# \qquad \qquad \qquad \quad cos( {7\pi}/6 ) \ = \ - \sqrt{3} / 2, \qquad \qquad sin( {7\pi}/6 ) \ = \ - 1 / 2. \qquad \quad (4) #
# "So, substituting the trig results we have in eqns. (3) & (4), into" # # "our original eqn. (1), we have now:" #
# \qquad \qquad \qquad e^{ {13\pi}/4 i } - e^{ {7\pi}/6 i } \ = #
# [ cos( {13\pi}/4 ) + cos( {7\pi}/6 ) ] - [ sin( {13\pi}/4 )+ sin( {7\pi}/6 ) ] i \ = #
# \qquad \qquad \qquad \qquad [ - sqrt{2} / 2 - \sqrt{3} / 2 ] - [ - \sqrt{2} / 2 - 1 / 2 ] i \ = #
# \qquad \qquad \qquad \qquad \qquad - 1/2 ( [ sqrt{2} + \sqrt{3} ] - [ \sqrt{2} + 1 ] i ). #
# "This is our answer." #
# "So, summarizing:" #
# \qquad \qquad \qquad \ \ e^{ {13\pi}/4 i } - e^{ {7\pi}/6 i } \ = \ - 1/2 ( [ sqrt{2} + \sqrt{3} ] - [ \sqrt{2} + 1 ] i ). \qquad \ \ square #
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7